Etude phytochimique et activités antioxydante et antiinflammatoire de la Withania frutescens. - Benhamdi, Alaa Eddine (My University, 2023)
Context: Since the beginning of time, people have used aromatic and medicinal plants as traditional medicine to cure various human illnesses. However, few studies have been carried out in the past to properly document, approve, validate and promote traditional knowledges. Objectives: This study, carried out at the Food Technology and Nutrition laboratory of the Faculty of Nature and Life Sciences at the Abdelhamid Ibn Badis University of Mostaganem, was performed from May 1, 2023 to July 30, 2023 to evaluate the phytochemical characteristics and the biological properties of Withania frutescens collected in April 2023 in the wilaya of Mostaganem. Materials and Methods: A phytochemical screening was undertaken followed by assays of polyphenols and flavonoids. The antioxidant activity was evaluated with the DPPH and FRAP tests and the anti-inflammatory activity was demonstrated with the hemolysis and protein denaturation tests. Results: The phytochemical screening concluded in a variety of bioactive substances (polyphenols, tannins, terpenes, coumarin, alkaloids, flavonoids, saponins). The quantitative evaluation revealed the richness of the plant in polyphenols and flavonoids, the antioxidant and anti-inflammatory activities are moderate. Conclusion: The ethanolic extract of Withania frutescens leaves contains biologically active compounds with antioxidant and anti-inflammatory properties. This plant can be used in traditional medicine to treat certain diseases.
Keywords: Withania frutescens; hemolysis; antiinflammatory activity; antihemolytic potential; antioxidant activity; phenolic compounds; phytochemistry; protein denatutation; Thermal shock; tanins; flavonoïdes